Our finest hour the triumphant spirit of the World War II generation - Jordan, Killian; Burrows, Barbara Baker ([New York] Time, Inc. Home Entertainment, 2000)
Presents touching stories that showed America's indomitable spirit as the United States fought for life and liberty during World War II.
1. The beginning. -- 2. Home front. -- 3. The lonely. -- 4. Fighters. -- 5. Women at war. -- 6. Entertainers. -- 7. The wounded. -- 8. The storytellers. -- 9. The lost. -- 10. The end. -- 11. Coming home. -- 12. Chronology. -- 13. Resources.
"With an introduction by Bob Greene."--Cover
CSSP-7618 donated by Reynaldo G. Alejandro, UP MLS 1967.
Keywords: World War, 1939-1945 -- United States; World War, 1939-1945 -- Pictorial works